Struktur komunitas tiram dagingdi perairan estuaria Kuala Gigieng, Kabupaten Aceh Besar, Provinsi Aceh - Chitra Octavina; Fredinan Yulianda; Majariana Krisanti (Depik, 2014)
Abstract. The oysters (Ostreidae) isone of economically important bivalves for urban community in Kuala Gigieng, Aceh Besar District. Presently, the quality and quantity of oyster is decreased over the years by intensive exploitation and water pollution. Therefore, theobjective of the present study was to analyze population structure and habitat condition of oystersin estuary area of Kuala Gigieng, Aceh Besar District, Aceh Province. The sampling was conducted at three locations during August to September 2013. The sampling locations were determined based on anthropogenic activities. A total of two genus of oysters were recorded during the study i.e Crossastrea with four species (C. gigas, C. iridescens, C. angulata, C. virginica) and and Ostrea edulis with one species (O. edulis). The highest density (39 ind m-2)of oysters were found at undisturbed and less pressure environment. The distribution pattern of Ostreidae in the Kuala Gigieng water was clustered where frequency of occurrence wasin small class size of 24 mm to 37.20 mm with optimum harvested of 32.27 mm. The growth of the oysters was relatively slow as shown by the maximum length (Lmaks) that can only reach 37.91-72.81 mm within 0 to 3.42 years. Generally, oysters population structure and habitat conditions in Kuala Gigieng Water was declined over the yeras. Therefore, it is a crucially needed to plan a management strategy for oysters with regulation on fishing, shellfish farming and waste disposal regulation to ensure the oysters population remains sustain.Keywords : Environment factors; fishing, growth; Kuala Gigieng; Oyster; population structureAbstrak. Tiram daging (Ostreidae) merupakan salah satu kerang yang memiliki  nilai ekonomi penting bagi masyarakat Kuala Gigieng. Namun, kualitas dan kuantitas tiram menurun akibat eksploitasi dan pencemaran perairan. Penelitian ini bertujuan untuk menganalisis struktur populasi dan kondisi habitat tiram di perairan estuaria Kuala Gigieng Kabupaten Aceh Besar, Provinsi Aceh. Sampling dilakukan pada tiga lokasi selama bulan Agustus hingga September 2013.Hasil penelitian menunjukkan bahwa terdapat dua genus tiram di perairan Kuala Gigieng yaitu Crassostrea dan Ostrea dengan total 5 spesies (C. gigas, C. iridescens, C. angulata, C. virginica and O. edulis). Kepadatan tertinggi berada pada lokasi yang tekanan penangkapan dan lingkungannya yang rendah. Pola penyebaran tiram daging di Kuala Gigieng cenderung mengelompok. Frekuensi ukuran selang kelas tiram terbanyak yang ditemukan yaitu 24-37,20 mm dengan ukuran layak tangkap yaitu 32,27 mm. Pertumbuhan tiram daging di Kuala Gigieng tergolong lambat, hal ini ditunjukkan dengan panjang maksimal (Lmaks) yang mampu dicapai kerang ini hanya 37,91-72,81 mm dalam waktu 0-3,42 tahun. secara keseluruhan, struktur populasi tiram daging dan kondisi habitat di Kuala Gigieng mulai menurun. Oleh karen itu, diperluka pengaturan pengelolaan sumberdaya tiram dengan melakukan pengaturan penangkapan, budidaya tiram, dan pembuangan limbah agar sumberdaya tiram di Kuala Gigieng tetap lestari.Kata kunci : Faktor lingkungan; Kuala Gigieng; penangkapan; pertumbuhan; struktur populasi; tiram daging,